A novel fiber-shaped asymmetric supercapacitor prepared by twisting carbon fiber/carbon nanotube/MnO2 and carbon fiber/carbon nanotube/polypyrrole electrodes+. (20th January 2021) - Cen, Tian; Chen, Liang; Zhang, Xuejun; Tian, Yanhong; Fan, Xinxiao
Highlights: The carbon fibers (CF) modified with carbon nanotubes (CNT) conductive network were realized through low-potential electrophoretic deposition. CF/CNT/MnO2 as positive electrode and CF/CNT/PPy as negative electrode were fabricated using simple electrochemical methods. An all solid state, a novel fiber-shaped asymmetric supercapacitor (n-FASC) was assembled by twisting the positive and negative electrodes with PVA-LiCl gel electrolyte. The n-FASC exhibited high energy density, excellent rate capability and mechanical stability, which can improve extremely potential for portable and wearable electronics. Abstract: In the study, a novel fiber-shaped asymmetric supercapacitor with high specific capacitance has been successfully constructed by twisting two self-made composite electrodes. Prior to manufacturing these electrodes, carbon nanotube is first deposited on carbon fiber by electrophoretic deposition to obtain carbon fiber/carbon nanotube composites. Subsequently, the positive and negative composite electrodes are prepared by the electrochemical deposition of manganese dioxide and electrochemical polymerization of polypyrrole, respectively. As a result, the novel fiber-shaped asymmetric supercapacitor performs a wide potential window of 1.7 V and a high energy density of 22.8 μWh cm −1 at the current density of 0.5 A g −1 . Meanwhile, it still maintains great capacitance retention of 91.6% and 86.1% from 500 bending repetitions and 5000 cycles, respectively, which is due to the excellent flexibility and long cycle life. It is significant that the promising performance of the novel fiber-shaped asymmetric supercapacitor is of greatly potential for portable and wearable electronics in the future. Graphical abstract: Importantly, carbon nanotubes (CNT) as conductive networks that can effectively improve the conductivity of the electrodes are grown on the surface of carbon fibers (CF). The composite electrodes, CF/CNT/MnO2 and CF/CNT/PPy, are fabricated via facile electrochemical methods. A novel fiber-shaped asymmetric supercapacitor (FASC) is successfully constructed by twisting the positive and negative electrodes with PVA-LiCl gel electrolyte, which performs excellent electrochemical properties and high flexibility. Image, graphical abstract